Local Government Policy on The Impact of Climate Change in Coastal Regions Based on The Concept of Green Autonomy (Environmental Autonomy) - Kholik, Saeful; Nurlinda, Ida; Muttaqin, Zainal; Priyanta, Maret; Jibril, Abubakar Muhammad (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2025)
The current centralized regime is preventing the implementation of climate change policy in line with the needs of affected regions. Consequently, many regions with distinctive coastal and small-island characteristics have been adversely affected by centralized policy largely due to a lack of regional government authority to establish climate change mitigation policy tailored to local needs. In this context, mitigation efforts based on green autonomy, namely the authority of regional government to establish climate change mitigation policy, are essential. Therefore, this research aims to identify the form of regional government policy addressing the impacts of climate change in coastal and small island regions, based on environmentally friendly autonomy. A doctrinal legal method was used with a descriptive-analytical approach, specifically a juridical-normative analysis that provides a descriptive analysis of regional government authority in climate change prevention. The results showed that the concept of climate change based on green autonomy emphasizes regional authority, independence, and independence in environmental management, particularly climate change efforts. This approach is operationalized by establishing cross-sectoral policy across structured and non-structured stages, starting with preparing coastal spatial plans consistent with regional interests without excluding national objectives. In conclusion, the concept of green autonomy offers a value contribution for government consideration in establishing climate change mitigation policy, and represents a new legal development for regional government in implementing concurrent authority matters.